Program Bahasa Indonesia bagi Penutur Asing (BIPA) di Universitas Fatoni, Thailand - Ku-Ares Tawandorloh; Islahuddin Islahuddin; Devita Cahyani Nugraheny (Indonesian Language Education and Literature, 2021)
This study aims to provide an overview of Indonesian for Foreign Speakers (BIPA) learning in the Indonesian Language Concentration, Malay Language Department, Fatoni University. This study uses a qualitative descriptive method. Data were obtained from BIPA lecturers, managers of the Indonesian Language Concentration at Fatoni University, documents, and various events in this program. Data analysis uses include data collection, data reduction, data presentation, and concluding. The study results show that BIPA learning has been growing in Thailand, and there have been BIPA lessons at the university level, one of which is Fatoni University. BIPA learning at Fatoni University has been managed with good education management, including institutions, curriculum, teachers, teaching materials, learning methods, and students.Penelitian ini bertujuan untuk memberikan gambaran pembelajaran Bahasa Indonesia bagi Penutur Asing (BIPA) di Konsentrasi Bahasa Indonesia, Jurusan Bahasa Melayu, Universitas Fatoni. Data penelitian deskriptif kualitatif inidiperoleh dari pengajar BIPA, pengelola Konsentrasi Bahasa Indonesia di Universitas Fatoni, dokumen, dan berbagai peristiwa di program ini. Analisis data meliputi: pengumpulan, reduksi, dan penyajian data, serta penarikan simpulan. Hasil penelitian menunjukkan bahwa pembelajaran BIPA sudah semakin berkembang di Thailand dan sudah ada pembelajaran BIPA di tingkat perguruan tinggi, salah satunya di Universitas Fatoni. Pembelajaran BIPA di Universitas Fatoni sudah dikelola dengan manajemen pendidikan yang baik, meliputi kelembagaan, kurikulum, pengajar, materi ajar, metode pembelajaran, dan mahasiswa.